Kajian Etnobudaya dan Etnomatematika pada Alat Musik Sarune Etek di Samosir - Silitonga, Dwi Ramawati; Rutmasari Silaban; Deliana Orcin Kahar; Friska Ledina Situngkir (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This research explores the Sarune Etek, a traditional wind instrument from Samosir, through ethnocultural and ethnomathematical lenses. Beyond its musical function, Sarune Etek represents a cultural identity of the Batak Toba community and embodies embedded mathematical principles in its physical structure, proportional design, tonal system, and rhythmic patterns. The study applies a qualitative approach through literature analysis, visual observation, and contextual interpretation. The ethnomathematical perspective reveals geometric forms, proportional ratios, quadratic patterns in air column variation, and periodic rhythmic structures. The results indicate that Sarune Etek can serve as an effective contextual medium for teaching mathematical concepts while simultaneously preserving local cultural heritage.